Synergistic enhancement: Ammonium polyphosphate's impact on hybrid coating performance against corrosion and fire - Siti Maznah, Kabeb; Azman, Hassan; Faiz, Ahmad (Wiley, 2024)
This research demonstrated the impact of ammonium polyphosphate (APP) content on corrosion resistance and flame retardancy properties of hybrid graphene oxide/halloysite/intumescent flame retardant (GO-HNT-IFR) coatings. Electrochemical impedance spectroscopy studied indicates that the GO0.6-H0.3 coating exhibited superior corrosion resistance (Rct = 2.490 × 109 Ω·cm) compared with hybrid GO-HNT-IFR coatings. Tafel polarization data revealed a decrease in polarization resistance, Rp simultaneously increases the corrosion rate, Rcorr of the epoxy coatings containing APP compare with GO0.6-H0.3 coating. Salt spray test result demonstrated that all epoxy coating filled with hybrid nanofillers maintained excellent surface integrity, preventing corrosion for up to 500 h under controlled accelerated corrosive conditions. A reasonable increment of limited oxygen index up to 12.5% was reported by the addition of 1 phr APP, indicating its best flame retardancy and thermal stability properties among coating samples. The appropriate addition of APP (1 phr) enhanced the flame retardancy and thermal stability properties of hybrid GO-HNT-IFR coatings to a certain extent but it is impaired by increasing the APP loading. Transmission electron microscopy results validated the formation of aggregation at high APP loading, consequently affecting coating performances as well as its adhesion strength.